Accumulated or continuous exercise for glycaemic regulation and control: a systematic review with meta-analysis. Issue 1 (17th December 2018) - Shambrook, Philip; Kingsley, Michael; Taylor, Nicholas; Gordon, Brett
Abstract : Objective: To compare the effectiveness of accumulating exercise in multiple bouts of at least 10 min throughout a day with exercise completed in a single bout (continuous or interval), or no exercise, on glycaemic control and regulation in inactive people without diagnosed glycaemic dysfunction. Design: Systematic review and meta-analysis. Data sources: Seven electronic databases were searched: CINAHL (EBSCO), Cochrane Library, EMBASE (Ovid), MEDLINE 1948-(Ovid), SCOPUS (Elsevier), SPORTDiscus (EBSCO) and Web of Science (ISI) with no restrictions on date and included all titles indexed up to February 2018. Eligibility criteria for selecting studies: Articles reporting insufficiently active adults (19 to 64 years) without metabolic dysfunction, measuring glycaemic control or regulation following at least 6 weeks of aerobic exercise. Results: Only one study compared accumulated exercise to single-bout exercise with no significant effect on fasting glucose (95% CI: −0.04 to 0.24 mmol·L -1 ) or fasting insulin (95% CI: −1.79 to 9.85 pmol·L -1 ) reported 48 hours after the final bout. No studies compared accumulated exercise with no-exercise. Compared with no-exercise, single-bout exercise reduces insulin resistance (mean difference (MD): −0.53 pmol·L -1 ; 95% CI: −0.93 to −0.13). Insulin resistance was clearly reduced with moderate-intensity (−0.68 (−1.28 to −0.09)) but not with high-intensity (−0.38 (−1.20 to 0.44)) exercise. Single-bout exercise was not statistically more beneficial than no-exercise for glycated haemoglobin (HbA1c ) (MD: −0.11 %; 95% CI: −0.24 to 0.02) in metabolically healthy individuals. Summary/conclusion: The glycaemic response to accumulated exercise or single-bout exercise might not be different, however exercise intensity might influence the mechanisms generating the response. PROSPERO registration number: CRD42015025042.